A brief historical outline of the development of labor analgesia - Michalczyk, Michał; Torbé, Dorota; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Birth of a child is an unique time in the life of every woman. Unfortunately, labor is often one of the most painful and traumatic experiences suffered in woman’s life. In the modern obstetrics pain of labor and methods of its mitigation are the main problem for both, patients and medical staff. In this paper the most important steps of the development of labor analgesia were described.